Cost Efficiency of Ballast Water Treatment Systems Based on Ultraviolet Irradiation and Electrochlorination - Vorkapić, Aleksandar; Radonja, Radoslav; Zec, Damir (Promet - Traffic&Transportation, 2018)
Having come into effect, the International Convention for the Control and Management of Ships’ Ballast Water and Sediments of 2004 requires ships to process their ballast water in accordance with specific standards. Different processing methods require different use of ship power, thus affecting fuel oil consumption, ships’ energy efficiency, and the ship economics in general. This paper presents the analysis and comparison of the economic viability of systems using two dominant ballast water treatment methods on merchant ships. The cost effectiveness of these methods, UV irradiation and electrochlorination, is compared to the standard efficiency of ballast water exchange using sequential flow method as a reference. The process efficiency is measured through fuel oil consumption on board. Taking into account possible variations in efficiency due to different designs and environmental constraints and assumptions, the findings are in favor of the electrochlorination method.